Sustainability reporting trends: A systematic literature network analysis - Vasyl Hyk; Oleh Vysochan; Olha Vysochan (Comparative Economic Research. Central and Eastern Europe, 2023)
Compiling and submitting sustainable development reports is a key area for reforming corporate reporting in light of the implementation of the Sustainable Development Goals. In recent years, the share of companies that report sustainable development and corporate social responsibility has grown significantly. Thus, the study of the definition of the conceptual apparatus is important. The article aims to study the quantitative and qualitative structure of the documentary flow of scientific periodicals, the main areas of research, and development trends and. It also presents the results of a systematic review of publications on "sustainability reporting". The study used bibliometric analysis of scientific periodicals from the Scopus scientometric database between 2011-2021. The scientific papers selected by the keyword "sustainability reporting" were exported for processing in the VOSviewer and R (bibliometrix package) computer programs. Based on the results of quantitative analysis, 625 publications were accepted, most of which were scientific articles. The main areas of research on sustainability reporting in accounting are sustainable development, sustainability, decision-making, sustainability reporting, and accountability. The study also made it possible to identify the authors and research schools that have made the most significant contribution to this topic, and to establish geographical clusters in the context of countries around the world that work closely with each other and the highest-rated journals. The originality of this study is that it helps to create a conceptual framework. It should guide the definition of future research, and it is designed to provide qualitative new insight into the role of sustainable development reporting. The article provides an opportunity to fill the gaps in quality research on sustainable development reporting. The main conclusions of this article will help researchers to expand their knowledge in this area through retrospective analysis of the research results.
Keywords: M41; Q01; Q56; 330; sustainability reporting; accounting; CSR; bibliometric analysis; network analysis